On the Construction of Colored Plane Crystallographic Patterns - De Las Peñas, Ma. Louise Antonette N (Archīum Ateneo, 2001)
In this paper, we present an approach to the construction of perfect and non-perfect colorings resulting from plane crystallographic groups. In particular, we consider colored patterns that arise with symmetry group normal in the symmetry group of the uncolored pattern.